WOMEN IN THE DOZO BROTHERHOOD IN IVORY COAST, FROM YESTERDAY TO TODAY: BETWEEN ANCESTRAL VALUES, MUTATIONS, STAKES AND POLITICAL TENSIONS - DATRO, Okobé Noël; Barnabé, ADOFFI Ange (IJRDO - Journal of Social Science and Humanities Research, 2022)
Appearing in West Africa, in Western Sudan, in the thirteenth century, at the birth of the Mali Empire, the Dozo brotherhood obeys a set of codes of good conduct. In particular, women play a leading role despite their status as initiates or not to dozoya. As in any traditional society in Africa, they are subject to the weight of many constraints imposed by the laws, customs and traditions established by initiatory rituals. The division of labour, as a general rule, is unfavourable to them, to the point where, in addition to domestic tasks, they ensure the supply of water, firewood, maintain a personal field and the education of children is devolved to them. Adherence to the Dozo culture distinguishes them from others and gives them a special status. From then on, they gained a less unequal social status compared to the uninitiated and participated in certain debates in the brotherhood. Unfortunately, today, these traditional values are crumbling because of the profound changes born in contact with the so-called modern Western civilizations that call into question the functioning of the brotherhood, because qualified as primitive civilizations, in a new world order. This article aims to highlight the role of the women of the Dozo brotherhood and the impact of so-called modern civilizations, political issues and tensions in Côte d’Ivoire in recent decades. Our methodology consisted in mobilizing information from books and oral testimonies in the field of oral investigations from a direct, semi-direct or free focus group. The objective cross-checking of this information and testimonies made it possible to understand the intensity of political tensions, the use of Dozo militias in national political affairs and the new functions of women in the Brotherhood.